ADVANTAGES AND DISADVANTAGES OF FUNCTIONS OF FINANCIAL AND ACCOUNTING SYSTEMS USED IN ACCOUNTANCY - Wioletta Świeboda (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
The need of collecting information about business units grows together with economic progress. Accounting is the source of this data without which no company would be able to conduct business activity. The data is considered to be the business language home and abroad, because it represents all the financial results by means of figures. The financial and accounting systems are being progressively introduced together with regulations aimed at making an accountant’s job easier. The systems available on the market vary from very simple ones built upon Excel spreadsheets, more advanced systems for small and medium sized enterprises developed by COMARCH-CDN (OPTIMA), Matrix.pl (Symfonia@) or InsERT (Rewior), to the most complex such as SAP, BAAN or IFS. As nowadays computers’ hard drives are used for keeping, registering and evidencing financial record 1 , tax declarations may be transferred directly to appropriate tax offices without the need for an accountant to leave his or her desk, and import and export of documents can be easily monitored. The electronic systems allow easy and fast access to archival information, easy correction of implemented data and offer a big amount of reminders and tips on how to deal with mistakes in accounting documents.